The new Oxford Shakespeare : the complete works - Shakespeare, William (OUP, 2017)
The Complete Works: Modern Critical Edition is part of the landmark New Oxford Shakespeare-an entirely new consideration of all of Shakespeare's works, edited afresh from all the surviving original versions of his work, and drawing on the latest literary, textual, and theatrical scholarship. In one attractive volume, the Modern Critical Edition gives today's students and playgoers the very best resources they need to understand and enjoy all Shakespeare's works. The authoritative text is accompanied by extensive explanatory and performance notes, and innovative introductory materials which lead the reader into exploring questions about interpretation, textual variants, literary criticism, and performance, for themselves. The Modern Critical Edition presents the plays and poetry in the order in which Shakespeare wrote them, so that readers can follow the development of his imagination, his engagement with a rapidly evolving culture and theatre, and his relationship to his literary contemporaries. The New Oxford Shakespeare consists of four interconnected publications: the Modern Critical Edition (with modern spelling), the Critical Reference Edition (with original spelling), a companion volume on Authorship, and an online version integrating all of this material on OUP's high-powered scholarly editions platform. Together, they provide the perfect resource for the future of Shakespeare studies.